Pemetaan Tipologi Kesalahan Teknis dalam Naskah Skripsi Mahasiswa Program Studi Pendidikan Guru Sekolah Dasar (PGSD) di Universitas X - Putra, Agung Dian; Pambudhi, Tegar; Muhisom, Muhisom; Afwan, Bahtiar (Universitas Muhammadiyah Magelang, 2026)
Thesis writing is a representation of students' academic abilities and professionalism in communicating in written form scientifically. However, in practice, technical aspects are often neglected compared to substantive aspects. This research aims to map the typology of technical errors in the thesis manuscripts of students in the Elementary School Teacher Education (PGSD) program at University X. The research approach uses a quantitative approach with a descriptive research type and descriptive-quantitative data analysis. The research results show that out of 15 categories of technical errors, there are three most dominant errors, namely: italicization, spacing, and citation format. In addition, issues were found regarding outdated references and inconsistencies in enumeration. These findings indicate the need to strengthen the understanding of the writing guidelines established by the University and to enhance students' precision thru the process of revising their writing and utilizing reference management technology.